Enhancing grain filling in rice using growth enhancers under water stress condition - Berahim, Zulkarami (2018)
Water stress is one of the key limiting factors in rice cultivation across the entire world. It reduces the production of rice, the income of farmers and stockpiles while increasing rice importation for drought stricken countries. Filled grain is the most affected part in rice plant especially during booting stage under water stress. There are various approaches for mitigation of plant under water stress. One of the approaches is through the use of growth enhancers by regulating physiological and biochemical attributes such as stomatal aperture and photosynthesis rate. The response of the rice plant variety MR219 subjected to different water regimes (well watered and water stressed) were investigated under both rain shelter and field condition. The objective of this study was to examine growth, physiological processes, biomass partitioning and yield determinants when rice plants were subjected to water stress condition. Biomass partitioning, harvest index and photosynthesis were reduced by 50% under water stress due to limitation in the efficiency of assimilate translocation. The results from the field study during prevailing drought condition had indicated the severity of yield losses at about 60-90% with drought imposed rice plant compared to the control. In the following studies short term measures to minimize the detrimental effect of water shortage on growth and rice plant development were carried out both under rain shelter and field conditions. The efficacies of growth enhancers (Vita-Grow®, epibrassinolide, spermine and pyroligneous acid) were evaluated on yield production of rice plants subjected to water stress condition. Among the growth enhancers studied, spermine was found to have the potential to mitigate the detrimental effect of water stress on rice plant. Yield and grain filling improvement of spermine treated plants were attributed to improved stomatal conductance, photosynthesis rate and assimilate partitioning. The application of spermine with double spray was found to be more effective in improving growth and development of water stressed rice plant. Following trials that were conducted under control environment, a series of field trials were conducted to validate the efficacy of spermine in reducing detrimental effects of water stress on yield of rice in different locations, planting seasons and prevailing climates. Application of spermine in three different locations representing our major national granary areas (MADA, KADA, IADA BLS) showed consistently higher rice yield compared to the control. Out of the three granary areas, the highest intensity of water stress was observed in KADA. Application of spermine showed significantly higher grain filling and yield in plant subjected to water stress condition. A trial was conducted under control environment in an attempt to investigate the response of spermine on sink strength and sucrose synthase (SUS) enzyme in relation to the development of rice plant under water stress condition in a control environment. The result suggested that higher grain filling rate and greater grain weight of spikelets were mainly attributed to more sink strength as a result of bigger sink size and high sink activity in spermine treatments.